2018
DOI: 10.1002/phar.2188
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Utility of Methicillin‐Resistant Staphylococcus aureus Nasal Screening for Antimicrobial Stewardship: A Review of Current Literature

Abstract: Significant clinical and financial consequences are associated with both inadequate and unnecessary exposure to broad‐spectrum antibiotics. As such, antimicrobial stewardship programs seek objective, reliable, and cost‐effective tests to identify patients at highest or lowest risk for drug‐resistant organisms to guide empirical antimicrobial selection. Use of methicillin‐resistant Staphylococcus aureus (MRSA) nasal screening to rule out MRSA in lower respiratory tract infections has led to significant reductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(21 citation statements)
references
References 57 publications
0
20
0
1
Order By: Relevance
“…A recent review describing MRSA nasal screening for ASP use across all infections recommends using this test for pulmonary infections but cautious use in BSIs because of the high risk of mortality with inappropriate antibiotic selection. 45 Additional sites that may be considered, despite a paucity of evidence, include intra-abdominal, skin and soft tissue, and urinary tract infections. 45…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review describing MRSA nasal screening for ASP use across all infections recommends using this test for pulmonary infections but cautious use in BSIs because of the high risk of mortality with inappropriate antibiotic selection. 45 Additional sites that may be considered, despite a paucity of evidence, include intra-abdominal, skin and soft tissue, and urinary tract infections. 45…”
Section: Discussionmentioning
confidence: 99%
“…45 Additional sites that may be considered, despite a paucity of evidence, include intra-abdominal, skin and soft tissue, and urinary tract infections. 45…”
Section: Mrsa Nasal Screening For Extrapulmonary Infectionsmentioning
confidence: 99%
“…This rationale has been applied to MRSA nasal colonization, being a predictor of subsequent pneumonia caused by MRSA (a systematic review found a pooled sensitivity and specificity of 40.3% (95%CI 17.4e68.4) and 93.7% (95%CI 77.1e98.4 for VAP), respectively [28]. Recent literature reviews on antibiotic stewardship suggest that a negative nasal screening test for MRSA could avoid unnecessary and costly antibiotics [28,29]; however, no parallel conclusions with Gram stain morphology could be drawn as we had no data to support such a claim. Additionally, Gram staining could be an initial test to indicate respiratory samples on which rapid molecular tests for MRSA could be performed [4].…”
Section: Discussionmentioning
confidence: 99%
“…Es una bacteria muy resistente al calor, la desecación y puede crecer en condiciones de alta salinidad. Esto facilita que el 20,00 % de la población sea portadora permanente de esta bacteria en fosas nasales y el 60,00 % actúan como portadores intermitentes (Carr et al 2018).…”
Section: Introductionunclassified